1984
DOI: 10.2136/sssaj1984.03615995004800050025x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Transformations under Zero and Shallow Tillage

Abstract: A field study was conducted with the objective of determining if differences occur in soil N transformations between zero and conventional tillage systems. Tillage comparisons of 2, 4, 12, and 16 yr duration were studied at four locations on Chernozemic soils in Western Canada. Determination of mineral N levels and immobilization of 15N‐urea fertilizer indicated that only slight, periodic, transient differences occurred between tillage systems. The degree of N mineralization‐immobilization turnover, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…2a-b) increased and then declined as the microbial biomass turned over and the labeled N was incorporated into more stable organic N fractions (Carter and Rennie, 1984b;Paul and Juma, 1981). A similar pattern is often found after addition of N-labeled plant residues (Amato and Ladd, 1980;Laddet al, 1981) or inorganic salts (Bristow et al, 1987;Carter and Rennie, 1984a;1984b;Ladd et al, 1977;Nannipieri et al, 1983). The incorporation of labeled N added to the meadow fescue in June (Fig.…”
Section: Microbial Biomass Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…2a-b) increased and then declined as the microbial biomass turned over and the labeled N was incorporated into more stable organic N fractions (Carter and Rennie, 1984b;Paul and Juma, 1981). A similar pattern is often found after addition of N-labeled plant residues (Amato and Ladd, 1980;Laddet al, 1981) or inorganic salts (Bristow et al, 1987;Carter and Rennie, 1984a;1984b;Ladd et al, 1977;Nannipieri et al, 1983). The incorporation of labeled N added to the meadow fescue in June (Fig.…”
Section: Microbial Biomass Nitrogenmentioning
confidence: 99%
“…Some of the fertilizer N is incorporated in non-harvested plant parts and soil microbial biomass. This N becomes progressively less available for mineralization due to chemical and biological stabilization processes (Allen et al, 1973;Broadbent and Nakashima, 1967;Carter and Rennie, 1984b;Legg et al, 1971;Smith et al, 1982). As a consequence, the contribution of the labeled N to subsequent harvests becomes smaller (Fredrickson et al, 1982;Hauck, 1971;Jansson, 1963;Power and Legg, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Although elimination of tillage can slow decomposition of residue, increase immobilization, and increase losses of N from the soil, Carter and Rennie (1984) concluded that replacement of the conventional shallow tillage techniques used on the prairies with NT would have minimal impact on the soil N cycle. Nevertheless, since cases of decreased plant N uptake continue to be reported under reduced tillage (e.g., McConkey et al 1996), the effects of tillage on soil N status warrant further investigation.…”
mentioning
confidence: 99%
“…Thus, conservation tillage practices can lead to pathogen inoculum concentrations several orders of magnitude greater than those found under conventional tillage (Khan, 1975;McFadden & Sutton, 1975) and, as a result, plant roots growing in the upper soil layers might be more prone to pathogen infection (Sturz et al, 1997). In contrast however, increased microbial biomass and activity in the top soil layers can give rise to greater root density and root activity (Lynch & Panting, 1980;Carter & Rennie, 1984), which may offset the damaging effects of disease on yield, and might also provide a highly competitive soil environment with resulting disease-suppressive effects (Chen et al, 1988).…”
Section: 31mentioning
confidence: 99%